Developmental Changes in Natural Viewing Behavior: Bottom-Up and Top-Down Differences between Children, Young Adults and Older Adults - Açık, Alper (Frontiers Research Foundation, 2010)
Despite the growing interest in fixation selection under natural conditions, there is a major gap in the literature concerning its developmental aspects. Early in life, bottom-up processes, such as local image feature – color, luminance contrast etc. – guided viewing, might be prominent but later overshadowed by more top-down processing. Moreover, with decline in visual functioning in old age, bottom-up processing is known to suffer. Here we recorded eye movements of 7- to 9-year-old children, 19- to 27-year-old adults, and older adults above 72 years of age while they viewed natural and complex images before performing a patch-recognition task. Task performance displayed the classical inverted U-shape, with young adults outperforming the other age groups. Fixation discrimination performance of local feature values dropped with age. Whereas children displayed the highest feature values at fixated points, suggesting a bottom-up mechanism, older adult viewing behavior was less feature-dependent, reminiscent of a top-down strategy. Importantly, we observed a double dissociation between children and elderly regarding the effects of active viewing on feature-related viewing: Explorativeness correlated with feature-related viewing negatively in young age, and positively in older adults. The results indicate that, with age, bottom-up fixation selection loses strength and/or the role of top-down processes becomes more important. Older adults who increase their feature-related viewing by being more explorative make use of this low-level information and perform better in the task. The present study thus reveals an important developmental change in natural and task-guided viewing.